2016
DOI: 10.1515/afepuc-2016-0007
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life of People with Disabilities from Sport Participation Point of View

Abstract: SummaryThe aim of the study was to compare the satisfaction with quality of life indicators (QoLI) and quality of life domains (QoLD) scores between people with physical disabilities (PPD) and people who are deaf or hard of hearing (PD/HH) from sport participation point of view. The study included 315 individuals with PPD (n = 150; male = 76) and PD/HH (n = 165; male = 85) divided into two groups of those who are regularly participating in sport and those who are not participating in any sport activity in thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 25 publications
(4 reference statements)
2
12
0
2
Order By: Relevance
“…On the other hand, the negative SWB was presented by both minority groups with sedentary behaviour with dissatisfaction with political situation and justice. People with physical disabilities showed in addition the negative SWB by dissatisfaction in their life with sport participation and deaf people dissatisfaction with finances like female high school students in the present study (Nemček 2016c).…”
Section: Discussionsupporting
confidence: 43%
“…On the other hand, the negative SWB was presented by both minority groups with sedentary behaviour with dissatisfaction with political situation and justice. People with physical disabilities showed in addition the negative SWB by dissatisfaction in their life with sport participation and deaf people dissatisfaction with finances like female high school students in the present study (Nemček 2016c).…”
Section: Discussionsupporting
confidence: 43%
“…It is difficult to understand that young people with PD and VD, who, despite their disability and who have some limited scope of motion, do not play sports or do exercise at least in their leisure time in order to at least partially compensate for the sedentary way of life and deficit of natural locomotion. Unfortunately, they probably do not realize that regular participation in sports activities can help them to improve the quality of their life, especially in the field of self-service activities, as well in all daily routine activities, which brings them, when they get older, more independence from other people, and later provides even more opportunities for inclusion through work activities despite their serious disability (Nemček & Labudová, 2009;Nemček, Labudová, & Kraček, 2012;Nemček, Labudová, & Oršulová, 2014;Nemček & Wittmannová, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…LS of growing age is strongly influenced by life experience and relationships, especially family relationships and health status . Many people with noncommunicable diseases (Nemček, Wittmannová, 2013;Onagbiye, Moss & Cameron, 2016) and disabilities (Rimmer et al, 2004;Kisvetrová et al, 2013;Kurková, 2010) have poor general health, limited community participation, and low quality of their life. However, few investigations have shown that participation in adapted sports has a positive effect on overall health (Nemček & Kručanica, 2014;Labudová, Nemček & Kraček, 2015), quality of life (Kurková & Maertin, 2014;Bendíková, 2014), quality of family life (Dobay & Bendíková, 2014) and quality of social life (Kurková, Válková & Scheetz, 2011) among people with disabilities.…”
Section: Introductionmentioning
confidence: 99%